Hospital survey on patient safety culture (HSOPSC): a multi-method approach for target-language instrument translation, adaptation, and validation to improve the equivalence of meaning for cross-cultural research (2020)
Background: The Hospital Survey on Patient Safety Culture (HSOPSC) is widely utilized in multiple languages across the world. Despite culture and language variations, research studies from Latin America use the Spanish language HSOPSC validated for Spain and the United States. Yet, these studies fail to report the translation method, cultural adaptation process, and the equivalence assessment strategy. As such, the psychometric properties of the HSOPSC are not well demonstrated for cross-cultural research in Latin America, including Peru. The purpose of this study was to develop a target-language HSOPSC for cross-cultural research in Peru that asks the same questions, in the same manner, with the same intended meaning, as the source instrument. Methods: This study used a mixed-methods approach adapted from the translation guideline recommended by Agency for Healthcare Research and Quality. The 3-phase, 7-step process incorporated translation techniques, pilot testing, cognitive interviews, clinical participant review, and subject matter expert evaluation. Results: The instrument was translated and evaluated in 3 rounds of cognitive interview (CI). There were 37 problem items identified in round 1 (14 clarity, 12 cultural, 11 mixed); and resolved to 4 problems by round 3. The pilot-testing language clarity inter-rater reliability was S-CVI/Avg = 0.97 and S-CVI/UA = 0.86; and S-CVI/Avg = 0.96 and S-CVI/UA = 0.83 for cultural relevance. Subject matter expert agreement in matching items to the correct dimensions was substantially equivalent (Kappa = 0.72). Only 1 of 12 dimensions had a low Kappa (0.39), borderline fair to moderate. The remaining dimensions performed well (7 = almost perfect, 2 = substantial, and 2 = moderate). Conclusions: The HSOPSC instrument developed for Peru was markedly different from the other Spanish-language versions. The resulting items were equivalent in meaning to the source, despite the new language and different cultural context. The analysis identified negatively worded items were problematic for target-language translation. With the limited literature about negatively worded items in the context of cross-cultural research, further research is necessary to evaluate this finding and the recommendation to include negatively worded items in instruments. This study demonstrates cross-cultural research with translated instruments should adhere to established guidelines, with cognitive interviews, based on evidence-based strategies.